Integrating Building Information Modelling, Lean Construction, And Quality Control: A Study Focused On Chinese Construction Engineering - Hongxia, Du; Al-Odaini, Aiman (Cuestiones de Fisioterapia, 2023)
The present study examines the implementation of building information modelling (bim) in chinese building engineering, explaining how technological innovation has transformed project execution and addressed issues facing the industry. The research emphasises bim as an internet-connected technology that is gaining significance in the construction industry because to its enhancement of presentation, collaboration, and effectiveness in operation. The study examines how bim enhances the dependability, efficiency, and environmental sustainability of construction projects in china. The results show that bim is a groundbreaking technology that works well to reduce design errors, raise estimate costs, and encourage collaboration between teams from different fields. It makes it easier for everyone to work together, cuts down on project delays, and makes the decision-making process for the building project better. The report also stresses how important it is for huge projects, like creating high-rise buildings and expanding urban recreational opportunities. In these projects, sophisticated design and tight deadlines mean that precision and good management are both important. Excessive costs associated with implementation, a lack of trained specialists, and the lack of completely standardised governing structures are some of the obstacles to broad acceptance that the research reveals, regardless of these benefits. Small organisations may not be equipped to capitalise on every advantage of incorporation of bim due to these constraints. The study found that the use of bim changes the appearance of building technology in china while rendering it more efficient, innovative, and environmentally friendly. To make the most of bim in the long-term, the industry needs consistent learning for workers, new policies, and defined regulations